INTERNALIZATION OF RELIGIC VALUES IN DEALING WITH THE COVID-19 PANDEMIC IN THE COMMUNITY OF GEMUTRI SUKOHARJO NGAGLIK SLEMAN YOGYAKARTA - Septoyadi, Zikry; Lastriana, Vita; Muzammil, Kholis (Hunafa: Jurnal Studia Islamika, 2021)
Abstrac Religiosity (religious adjective) is not synonymous with religion. A religious person should be a religious person at the same time. Covid-19 has not only damaged people's lives in the health and economic sectors, but religious activities in various areas have temporarily stopped carrying out religious activities in mosques and surrounding areas such as compulsory prayers, Friday prayers, yasinan, recitation, etc. Dusun Gemutri from the very beginning of the existence of Covid had confusion in deciding daily activities. This research uses a qualitative approach. The subjects of this research are the head of the hamlet, Pak RW, Pak RT, community leaders and part of the community. The object of this research is the Internalization of Religious Values ​​in Facing the Covid-19 Pandemic in the Community in Dusun Gemutri Sukoharjo Ngaglik Sleman Yogyakarta. The technique used in determining the subject of this study using purposive technique and using the snowball sampling method. Data collection techniques with observation, interviews and documentation. The data analysis technique was carried out by means of data reduction, data presentation, and drawing conclusions Based on the results of the analysis and discussion of the internalization process of religious values ​​in the Gemutri Sukoharjo Ngaglik hamlet, it is very different from before the covid pandemic and after the pandemic, because at the beginning of the Covid pandemic yesterday the community was very scared and religious activities such as Mujahadah, Yasinan, etc. Everything has been stopped temporarily but the very interesting thing in the Gemutri Sukoharjo Ngaglik Sleman community is when there is Covid in the cultivation of Yauti religious values ​​which usually do not have tasbih prayer activities, when Friday prayers in Friday prayers use prayers Qunud and Carry out Istighosah activities. Keywords: Religious Values ​​and Covid-19